Cytotoxicity Assessment in Sesame Leaves Using Human Cancer Cell Lines - Dr. Mukta Nagpurkar; Dr. Neeta M. Patil (International Journal of Pharma and Bio Sciences, 2023)
Sesamum indicum L. (Pedaliaceae) seeds are used worldwide for their oil content. It is one of the oldest condiments and the world’s most important oil seed crop. The primary marketable products of sesame, whole seeds, seed oil, and seed meal are well explored for their biochemical profiles. Different studies record various uses of sesame seed oil in culinary, nutritional science, ethnomedicine, cosmetics, and pharmaceutical industries. In addition, other secondary metabolites like flavonoids, alkaloids, tannins, saponins, steroids, terpenoids etc., are detected in sesame seeds. These secondary metabolites are involved in various biological activities such as antioxidant, anti-bacterial, anti-diabetic, hypocholesterolemic, anti-tumour, anti-ulcer, antiinflammatory etc. The aim is to test the cytotoxicity of different extracts from leaves of white sesame var. JLT408 (Jalgaon Til 408, 2010). The objective is to perform in vitrocolorimetric assay using human cancerous cell lines. The adherent carcinoma cell line HEp – 2 (Human Epithelial type 2) and suspension lymphoma cell line Jurkat, Clone E6-1 were selected for the assay. The ethanol, methanol, aqueous extract, alkaloid extract and its ethyl acetate fraction all were subjected to cytotoxic assay using the MTT method. Cytotoxicity was tested as a dose-responsive assay using MTT(3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide) reagent. Alkaloid extract and its isolated fraction containing a mixed opiate azine named oxymorphone-naltrexonazine (OMNZ) showed the presence of cytotoxicity in two different types: adherent and suspension culture cell lines. The study indicated that cytotoxicity varies depending upon not only the concentration of extract but also the type of culture and cancer.